Maternal vaccination and protective immunity against Zika virus vertical transmission - Chao Shan (Nature Portfolio, 2019)
A Zika virus vaccine should protect the fetus during pregnancy. Here, using a live-attenuated Zika vaccine, the authors show that a higher neutralizing antibody titer is required to protect from in utero transmission than to protect non-pregnant mice and that a single maternal immunization protects the fetus from infection and disease.